ENHANCING LEARNING OUTCOMES IN CREATIVE AND ENTREPRENEURIAL PROJECTS THROUGH LOCAL POTENTIAL-BASED TEACHING MODULES - HASWAH HASWAH; HAMSU ABDUL GANI; RIANA T MANGESA (Pascasarjana Universitas Negeri Makassar, 2024)
Entrepreneurship education is a learning process that requires self-direction and self-management from students. The objectives of this study are (1) to determine student learning outcomes after using the Creative and Entrepreneurship Project Learning Module, and (2) to assess the improvement in student learning outcomes. This research is experimental in nature, employing a One Group Pretest-Posttest Design with one class utilizing the learning modules, administering a pretest at the beginning and a posttest at the end of the learning period. The subjects of this study were 35 students from class XI of Online Business Marketing at SMK 1 Bone Regency, selected through purposive sampling. The data analysis focused on the effectiveness of the learning module using the n-gain score test. The results indicated that (1) the learning outcomes of students in the field trials exhibited a very high category learning tendency with a percentage of 42.86%, and (2) the n-gain score in the experimental class was 0.48, suggesting a moderate improvement in learning outcomes. Therefore, it can be concluded that the use of Creative and Entrepreneurship Project Learning Modules based on Local Potential is more effective than previously used products.